AN ANALYSIS OF THE IMPLICATIONS OF THE GROWING TABLOIDIZATION OF NEWS COVERAGE ON DEMOCRATIC POLITICS - Nasser N. Alotaibi (European Scientific Journal, ESJ, 2013)
This study is a literature review to explore the effect of the growing tabloidization of news coverage on democratic politics. The study focuses on some important considerations, among which are three basic values of modern democratic societies, namely, freedom, justice and order, which it is vital to retain. While these basic values in mass media communication are not compromised, it is difficult to deny that the media, tabloid or not, cause a crisis in public life. This crisis means that ‘core values’ such as independence, diversity and objectivity risk being lost because of changes in the media. Such changes are due to pressures from the market and society, but these pressures have not been shown to hinder democratic life.